نموذج حلزوني ESP - سامي عبد العزيز المعموري (مجلة الفتح للبحوث التربوية والنفسية, 2023)
Abstract This paper is an abridgement of an MA thesis entitled " Evaluating the COURSE OF ENGLISH FOR THE STUDENTS IN COLLEGES OF PHYSICAL EDUCATION and Suggesting A New Up-to-date One " The study was carried out by Ahmed Khalis Sha'lan ( first researcher , a member of the Faculty of the College of Languages /University of Baghdad /Iraq ) and Asst. Prof. Sami Abdul-Aziz Almamuri ( second researcher, a member of the faculty of the college of Basic Education/University of Diyala /Iraq ). The thesis was submitted to the Council of the College of Education in Diyala University /Iraq .It was discussed on the 16th / 1 /2008 by an appointed examination committee and was marked as(Very Good ) ,and accordingly the researcher was awarded a Master Degree in Education / Methods of Teaching English as A Foreign Language . The study is essentially two-dimensional. On the one hand, it targeted on evaluating the COURSE OF ENGLISH FOR THE STUDENTS OF COLLEGES OF PHYSICAL EDUCATION (henceforth CESCPE ) ,( compiled Abdul-Razzak & Al-mufti 1987) to identify , according to certain criteria and through a critical analysis , the extent this supposed ESP course responds the EFL learners' needs in the colleges of education . On the other hand, it aims at suggesting an alternative ESP course thought to be able to respond the learner’s needs.